Prevalence and sociodemographic characteristics of functional impairment in community-dwelling older adults in China: a cross-sectional study - Yun Li; Li Zhang; Zhe Tang; Lina Ma; Pan Liu; Xiaxia Li; Wenhua Yu; Yaxin Zhang (BMJ Open)
Objectives Functional impairment is an early stage of disability, and timely identification and intervention are critical for the health of older adults. However, little is known about the functional impairment of Chinese older adults due to the absence of specialised assessment tools. This study aimed to explore the prevalence and socio-demographic characteristics of functional impairment in Chinese community-dwelling older adults using the Function Impairment Screening Tool (FIST), which was previously developed based on the Delphi method.Design Cross-sectional study.Setting Community-based.Participants The study included 6444 community-dwelling older adults from the China Comprehensive Geriatric Assessment Study.Results The FIST identified functional impairment in 31.3% of Chinese community-dwelling older adults. The prevalence was higher among women and individuals in rural areas and increased with age. Illiteracy, no spouse, living alone, poor self-reported health, low income, limited meat intake, less exercise, chronic diseases and geriatric syndromes were associated with functional impairment. Furthermore, after adjusting for related variables, functional impairment was independently associated with disability (OR=138.5, 95% CI 70.0 to 273.9), frailty (OR=13.7, 95% CI 10.3 to 18.3), immobility (OR=6.9, 95% CI 5.4 to 8.9), fractures (OR=2.2, 95% CI 1.5 to 3.3) and falls (OR=2.6, 95% CI 1.8 to 3.7).Conclusion Approximately one-third of Chinese community-dwelling older adults experienced functional impairment, and its prevalence was associated with socio-psychological characteristics, lifestyle, chronic diseases and geriatric syndromes.